2015
DOI: 10.1177/1087054715580845
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Body Image in the Link Between ADHD and Depression Symptoms Among College Students

Abstract: Body image appears to play a role in the association between ADHD and depression symptoms for college students. Implications for future research and clinical practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Finally, this study analyzed the relationship of the ASRS versions with other disorders and severity of dependence. Regardless of the version used, the relationships found by others were detected (Jacob et al, 2007; Jarret, 2016; Jarrett & Ollendick, 2008; Lee et al, 2011; Mitchison & Njardvik, 2019; Semeijn et al, 2015; Van Eck, Morse, & Flory, 2018). However, in the regression models, it was observed that the explanatory power of the model for dependence on alcohol improved when the scores on the hyperactivity/impulsivity dimension were entered.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Finally, this study analyzed the relationship of the ASRS versions with other disorders and severity of dependence. Regardless of the version used, the relationships found by others were detected (Jacob et al, 2007; Jarret, 2016; Jarrett & Ollendick, 2008; Lee et al, 2011; Mitchison & Njardvik, 2019; Semeijn et al, 2015; Van Eck, Morse, & Flory, 2018). However, in the regression models, it was observed that the explanatory power of the model for dependence on alcohol improved when the scores on the hyperactivity/impulsivity dimension were entered.…”
Section: Discussionmentioning
confidence: 81%
“…The population study done by Kessler et al (2006) demonstrated that individuals with ADHD have a probability of developing other disorders varying from 2.7 to 7.5 for mood disorders, 1.5 to 5.5 for anxiety disorders, and 1.5 to 7.9 for substance disorders. Other studies have also shown that ADHD symptoms are related to depression (Semeijn et al, 2015; Van Eck, Morse, & Flory, 2018) and anxiety (Jacob et al, 2007; Jarret, 2016; Jarrett & Ollendick, 2008; Mitchison & Njardvik, 2019). ADHD in childhood is linked as a risk factor for adult drug use (e.g., Charach, Yeung, Climans, & Lillie, 2011; Groenman et al, 2013; Lee, Humpherys, Flory, Liu, & Glass, 2011).…”
mentioning
confidence: 94%
“…7,43,44 Body image dissatisfaction and depression not only act as single factors that can impede success in a patient's weight loss journey but also interact with each other in a bidirectional manner. 11,12 In fact, poor body image has been proposed to mediate the relationship between obesity and psychological symptoms of depression and low self-esteem. 45 Bodily dissatisfaction and psychological distress can act as a trigger for stress-related eating behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…10 Specifically, individuals with poorer body image have been found to have a higher likelihood of depression and depressive symptoms. 11,12 It has been estimated that 25-30% of bariatric surgery patients report clinically significant depression that has been found to be higher than nonsurgery-seeking adults with morbid obesity in the most frequently prescribed. 18 Furthermore, patients concerned with their body image were more likely to be taking psychotropic medications and to be involved in outpatient therapy.…”
Section: Introductionmentioning
confidence: 99%
“…6 Similarly, the presence of body image disorders among college campuses also poses a threat to the severity of mental health disorders such as depression. 7 College students are at risk for developing a new or worsening eating disorder with up to 40% of female college students reporting weight management behaviors, body image concerns, and out of control eating. 8 Another disorder requiring attention and support for college students is attention-deficit/hyperactivity disorder (ADHD).…”
Section: Introductionmentioning
confidence: 99%